Employment Branding in the Knowledge Economy - Ewing, Michael; Pitt, Leyland; De Bussy, Nigel (N T C Publications Ltd, 2002)
For most of its existence advertising has focused on attracting customers. More recently, enlightened organisations have recognised the need to expand their communications efforts to incorporate all stakeholders, not only end-users. The marketing literature has begun to address stakeholder theory, as well as advertising's indirect and internal audiences, but more as a secondary consideration or by-product of consumer marketing. However, the anticipated permanent shortage of skilled workers in the new economy creates unique challenges for knowledge-based organisations in particular, who will increasingly need to differentiate themselves in order to successfully attract talented employees. As a result, more and more firms may turn to advertising to create 'employment brands' and thereby offer an enticing vocational proposition that is compelling and differentiated. In response to this emerging trend, this article begins by introducing stakeholder theory into a marketing framework. We then classify existing approaches to employment branding by identifying three basic types of employment advertising strategies. In closing, managerial implications are discussed, an agenda for future research is proposed and conclusions are drawn.